Protein Phosphatase 2A as a Therapeutic Target in Acute Myeloid Leukemia - Arriazu, Elena; Pippa, Raffaella; Odero, María D. (Frontiers in Oncology, 2016)
Acute myeloid leukemia (AML) is a heterogeneous malignant disorder of hematopoietic progenitor cells in which several genetic and epigenetic aberrations have been described. Despite progressive advances in our understanding of the molecular biology of this disease, the outcome for most patients is poor. It is, therefore, necessary to develop more effective treatment strategies. Genetic aberrations affecting kinases have been widely studied in AML; however, the role of phosphatases remains underexplored. Inactivation of the tumor-suppressor protein phosphatase 2A (PP2A) is frequent in AML patients, making it a promising target for therapy. There are several PP2A inactivating mechanisms reported in this disease. Deregulation or specific post-translational modifications of PP2A subunits have been identified as a cause of PP2A malfunction, which lead to deregulation of proliferation or apoptosis pathways, depending on the subunit affected. Likewise, overexpression of either SET or cancerous inhibitor of protein phosphatase 2A, endogenous inhibitors of PP2A, is a recurrent event in AML that impairs PP2A activity, contributing to leukemogenesis progression. Interestingly, the anticancer activity of several PP2A-activating drugs (PADs) depends on interaction/sequestration of SET. Preclinical studies show that pharmacological restoration of PP2A activity by PADs effectively antagonizes leukemogenesis, and that these drugs have synergistic cytotoxic effects with conventional chemotherapy and kinase inhibitors, opening new possibilities for personalized treatment in AML patients, especially in cases with SET-dependent inactivation of PP2A. Here, we review the role of PP2A as a druggable tumor suppressor in AML.